Visibilizing and managing paradox: Redefining the role of non-executive directors - Pina e Cunha, M.; Leite, A. N.; Rego, A.; Hernández-Linares, R. (Corporate Governance, 2024)
Purpose: This paper aims to discuss the work of non-executive directors (NEDs) as inherently paradoxical. Paradox refers to the presence of persistent contradictions between interdependent forces. Those persistent tensions are explored, and approaches are indicated to stimulate the adaptive use of paradoxes as forces of innovation and renewal. Design/methodology/approach: This conceptual approach can be read as an invitation for corporate governance scholars to embrace the logic of paradox to expand the understanding of this topic. Paradox is not conceptualized as an alternative to dominant structural views, including board composition, but as a complementary conceptual perspective, a meta-theoretical lens to shed light on the tensions inherent to governance. Findings: The authors propose that paradox theory offers a fresh conceptual lens to study the role of NEDs. This approach may help NEDs to turn tensions and paradoxes visible to develop a rich understanding of their work, as well as helping them navigate the complexities of organizing, a process rich in inherent paradoxicality. Originality/value: Organizational paradox theory is a bourgeoning field of study, but the conceptual lens of paradox has still been underexplored in the study of corporate governance.